Управління капіталом у контексті забезпечення конкурентних переваг суб’єкта піlприємницької діяльності роздрібної торгівлі - Дядін, А. С.; Diadin, A. S.; ORCID: http://orcid.org/0000-0002-2277-2795; Бобро, Н. В.; Bobro, N. V.; ORCID: http://orcid.org/0000-0002-8350-3695 (Право і безпека. - 2021. - № 1 (80). - С. 35-41., 2021)
Проаналізовано загальні особливості формування та функціонування підприємницького капіталу. Обґрунтовано основні етапи оптимізації фінансової структури капіталу підприємств як специфічного об’єкта антикризової підприємницької діяльності роздрібної торгівлі. Надано характеристику фінансового потенціалу як ключової ланки, що зумовлює вектор руху підприємницької діяльності. Визначено основні елементи як мінімізації витрат під час реалізації превентивних антикризових заходів, так і можливості протистояти конкурентним викликам шляхом оновлення системи виробництва. Доведено, що практичні шляхи реалізації антикризових заходів є пріоритетними і вирішальними для визначення ступеня життєздатності та перспектив розвитку суб’єкта, спрямованих на зростання його ринкової вартості, зміцнення фінансової потужності та нарощування фінансових резервів, які дозволять у майбутньому посилити захисні властивості.

It has been proved that capital is a resource that is accumulated and is involved in the processes of reproduction and growth of value through mutual conversion of its various types, which are invested in the creation of assets, which is the total amount of financial resources of enterprises. It has been demonstrated that it is possible to determine the most rational ratio of capital indicators calculated on the basis of factors of influence, risks and practical experience that brings the target capital structure as close as possible to its optimal value. Given that the capital structure affects the market value of the enterprise through the price of capital, the concept of capital structure is studied in the same theoretical complex with the concepts of capital value and market value of the enterprise. The analysis has demonstrated that the first stage of optimizing the financial structure of enterprise’s capital as a specific object of anti-crisis retail business allows to determine the presence or absence of capital volume for a particular business entity. If the answer is positive, the optimization of the ratio of all sources of capital is carried out within this volume. If the available amount of capital is insufficient, it is necessary to find out whether the company has the opportunity to expand it and the sources to accomplish it. The second stage – assessing the capital structure by the criterion of financial stability – is carried out by comparing the actual values of the ratio of the current assets of business entities in retail trade in equity with the “normal” value, where its minimum level is 0.1. The capital structure is assessed during the third stage from the standpoint of the value of capital. Appropriate calculations are made by using the weighted average cost of capital of a business entity. The capital structure is evaluated during the fourth stage in terms of its efficiency. The basis for assessing the structure of capital by the criterion of its effectiveness is the calculation of the effect of financial leverage in previous periods and determining the impact of individual factors (return on assets, weighted average cost of debt, share of debt and equity) on this effect by using the method of chain substitutions regarding the weighted average cost of borrowed capital adjusted for the net operating result of the investment, the value of leased fixed assets, the amount of rent, as well as the share of financial loans, trade payables and long-term credit in the form of leased fixed assets in total borrowed capital. Finally, the target-oriented capital structure is formed during the fifth stage, taking into account the obtained results of optimization according to all the criteria and features of the components of capital and the factors that affect them. The fulfillment of this stage requires a thorough development of specific measures that should allow to form the necessary capital structure of the business entity in retail.

Проанализированы общие особенности формирования и функционирования предпринимательского капитала. Рассмотрены основные этапы оптимизации финансовой структуры капитала предприятий как специфического объекта антикризисной предпринимательской деятельности розничной торговли. Охарактеризованы основные этапы оптимизации финансового потенциала как ключевого звена, приводящего вектор движения предпринимательской деятельности. Раскрыты основные элементы как минимизации затрат при реализации превентивных антикризисных мер, так и возможности противостоять конкурентным вызовам путем обновления системы производства. Показано, что практические пути реализации антикризисных мер являются приоритетными и решающими для определения степени жизнеспособности и перспектив развития субъекта, направленных на прирост его рыночной стоимости и наращивание финансовых резервов, которые позволят в будущем усилить защитные свойства.
Share capital management in the context of ensuring competitive advantages of the retail business entity
Управление капиталом в контексте обеспечения конкурентных преимуществ субъекта предпринимательской деятельности розничной торговли
Дядін, А. С. Управління капіталом у контексті забезпечення конкурентних переваг суб’єкта підприємницької діяльності роздрібної торгівлі / Андрій Сергійович Дядін, Наталія Валеріївна Бобро // Право і безпека. - 2021. - № 1 (80). - С. 35-41. - DOI: 10.32631/pb.2021.1.04.
Дядін, А. С. і Бобро, Н. В. (2021) «Управління капіталом у контексті забезпечення конкурентних переваг суб’єкта підприємницької діяльності роздрібної торгівлі», Право і безпека, 80(1), с. 35-41. doi: 10.32631/pb.2021.1.04.
Keywords: Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; капітал; підприємницька діяльність; оптимізація фінансової структури; антикризове управління; капитал; предпринимательская деятельность; оптимизация финансовой структуры; антикризисное управление; share capital; entrepreneurial activity; optimization of financial structure; anti-crisis management